Characterization of Si-based materials for surface micromachined microbolometer applications - Zhang, Guowei (2008)
In this thesis, the integration of CMOS devices with Si-based microbolometer sensor on the same silicon chip was studied. Silicon based material, Poly-Si and Poly-SiGe layers were deposited as the Infra-Red (IR) sensing film as well as the CMOS gate electrode. Microbolometer test structures and CMOS devices were fabricated using separately process flows. The CMOS devices were fabricated using the 2um N-well CMOS process modified by Shallow Trench Isolation (STI) for device isolation.